Teaching Speaking English Strategies For Indonesian Labors - Siti Sumihatul Ummah (Indonesian Journal of Education Methods Development, 2019)
The objectives of this research were to describe teaching Speaking English strategies used by the instructor for Indonesian labors, to investigate the instructor’s obstacles in teaching Speaking English, to know the instructor’s efforts in overcoming the obstacles, and to know the Indonesian labors’ respons in learning Speaking English at PT. Assanatama Karya Mandiri Surabaya. The research method was qualitative descriptive. The data sources were from the instructor and Indonesian labors. There were three ways to collect the data namely oberservation, interview, and documentation. The result of the research showed that there were six teaching strategies of Speaking English used by the instructor namely grammar translation method, communicative approach, audio-lingual method, role play method, demonstration method, and lecturing method. While the obstacles usually faced by the instructor in teaching Speaking English were the differences of Indonesian labors background, Indonesian labors difficulty in memorizing materials, arrangement of time allotment, indisciplinary of Indonesian labors, and Indonesian labors had low spirit in learning Speaking English. From these obstacles, the instructor overcame them by adapting her teaching strategy appropriately with games and songs, giving drilling in conversation section, giving interesting medias, collaborating other strategies in teaching Speaking English, and giving reward and pedagogy punishment.